DEVELOPMENT OF SCIENCE LEARNING MODULE BASED ETHNOSCIENCE ON JENANG KUDUS FOR CLASS VIII SMP/MTs - Khastuti, Khastuti; Prasetyo, Dody Rahayu (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Science learning will be more meaningful if there is continuity between the science material enjoyed and real-life activities in the student's environment. One of them is developing teaching materials that utilize local cultural wisdom that exists in the daily lives of students as learning resources in supporting the achievement of competencies and goals in science learning. This study aims to determine the development and placement of science learning modules based on the ethnoscience of jenang Kudus in additive substance. This research is a development or R&D research with a Thiagarajan 4D model  covering the stages of defining, designing (design), developing (development), and disseminating (disseminate), but this research is only limited to 3 stages, namely define (defining), design (designing), develop (development). The subjects of this research trial were 15 students of class VIII at SMP 4 Kudus. This research produces a product in the form of a module as a teaching material in science learning based on the ethnoscience of jenang Kudus on additive substance. Stages of design the cover using the Canva application and filling out the module using Microsoft Word. The module specifications include: the characteristics of the physical module, the material module, additive substance material, and the content module, which is based on ethnoscience. The modules developed can be very feasible to be used in learning, as shown by the results of validation by media experts and material experts who each obtained percentage results of 95.83% with "very good" and 84.44% in the "very good" category and for teacher and student responses to the development of this module obtained a percentage result of 90.33% respectively with the criteria of very good and 92.75% with the criteria of very good.